Acceptability and feasibility of a pilot randomized controlled trial of Narrative e-Writing Intervention (NeW-I) for parent-caregivers of children with chronic life-threatening illnesses in Singapore - Dutta, Oindrila (2022)
Narrative e-Writing Intervention (NeW-I) is a novel psycho-socio-spiritual intervention which aims to bridge gaps in paediatric palliative care by providing anticipatory grief support to parent-caregivers who are looking after their child with a chronic life-threatening illness in Singapore. This is done via a therapist-facilitated smartphone app that focuses on strengths and meaning derived from parents' caregiving journey. NeW-I is empirically informed by an international systematic review and a Singapore-based qualitative inquiry on the lived experience of parental bereavement and supported by anticipatory grief interventions literature for improving the holistic well-being for parent-caregivers of seriously ill children. NeW-I is implemented in Singapore as an open-label two-armed randomized controlled trial comprising an intervention and control group.